E.M. Forster thames and hudson - King, Francis . (New York, N.Y. : Thames and Hudson, 1988)
A biography of the English novelist, essayist, and literary critic known for such works as a "A Room With A View," "Howards End," and "A Passage To India."
Includes index.
Bibliography: p. 120-121.
All Ages.
Keywords: Forster, E. M. -- 1879-1970.; Forster, E. M. -- 1879-1970.; Novelists, English -- 20th century -- Biography; Authors, English